2019
DOI: 10.1002/elps.201800422
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the enantioselectivity of tetramethylammonium‐lactobionate chiral ionic liquid based dual selector systems toward basic drugs in capillary electrophoresis

Abstract: Recently, chiral ionic liquids (CILs) have received increasing interest in chiral separation by CE. Nevertheless, the lack of deep perception of the specific mechanism about CILs in CE for enantioseparation still perplexes a legion of researchers, despite the strenuous efforts. In this paper, a lactobionic acid based ionic liquid, tetramethylammonium‐lactobionate (TMA‐LA) was applied for the first time in CE to establish dual selector system with clindamycin phosphate (CP) for enantiomeric separation. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…CILs have attracted much attention for several applications, such as chiral solvents, asymmetric synthesis, a, recently, chiral CE for the separation of enantiomers. CILs are commonly used as chiral selectors, chiral ligands, and in the BGE, as listed in Table 2 [114–154]. ACILs such as the ones based on alkylpyridinium, alkyl imidazolium, and tetraalkylammonium are also used in CE separation with combinations of β‐CD derivatives and furnish a favored interaction with enantiomers.…”
Section: Electrophoretic Methods For Enantioseparationmentioning
confidence: 99%
See 1 more Smart Citation
“…CILs have attracted much attention for several applications, such as chiral solvents, asymmetric synthesis, a, recently, chiral CE for the separation of enantiomers. CILs are commonly used as chiral selectors, chiral ligands, and in the BGE, as listed in Table 2 [114–154]. ACILs such as the ones based on alkylpyridinium, alkyl imidazolium, and tetraalkylammonium are also used in CE separation with combinations of β‐CD derivatives and furnish a favored interaction with enantiomers.…”
Section: Electrophoretic Methods For Enantioseparationmentioning
confidence: 99%
“…The most typical ILs and CILs cations used for enantiomeric separations in CE are commonly used in combination with CDs and are based on tetrabutylammonium, tetramethylammonium, methylimidazolium, and their derivatives (Figure 3B) [117, 120, 124, 128130, 132, 138, 139, 142, 143, 146, 149, 151, 153]. These nitrogen‐based cations deeply influence the greenness of ILs, and most of them display toxic behavior due to their hydrophobicity.…”
Section: Electrophoretic Methods For Enantioseparationmentioning
confidence: 99%
“…The chiral recognition mechanisms by CILs have been reviewed [89]. Lactobionic acid-based CILs were evaluated as novel selectors in CE for the enantioseparation of basic drugs [90][91][92]. The enantiomer migration order could be correlated to the formation of hydrogen bonds established between the analyte enantiomers and the CILs in molecular modeling studies.…”
Section: Structures Of Selector-selectand Complexesmentioning
confidence: 99%
“…The obvious superiority of chiral ILs to equal ILs is due to their ability to gain an extra enantiomeric recognition, so separating ability, while maintaining a "system modification" capability [227]. Based on their potential, which is related to ability for recognitions on chiral separations, scientific interest in CILs has warmly increased [228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246]. In chiral separations studies, it is observed that the performance of the systems created by modifying ionic liquids with SPs enhances the enantiorecognition ability compared to conventional type stationary phases alone [247].…”
Section: Ionıc Liquids (Ils) As Chiral Additivesmentioning
confidence: 99%